The amino-terminal domain of GluA1 mediates LTP maintenance via interaction with neuroplastin-65 - Chao-Hua, Jiang; Wei, Mengping; Zhang, Chen; Shi, Yun Stone (Proceedings of the National Academy of Sciences - PNAS, 2021)
Long-term potentiation (LTP) has long been considered as an important cellular mechanism for learning and memory. LTP expression involves NMDA receptor-dependent synaptic insertion of AMPA receptors (AMPARs). However, how AMPARs are recruited and anchored at the postsynaptic membrane during LTP remains largely unknown. In this study, using CRISPR/Cas9 to delete the endogenous AMPARs and replace them with the mutant forms in single neurons, we have found that the amino-terminal domain (ATD) of GluA1 is required for LTP maintenance. Moreover, we show that GluA1 ATD directly interacts with the cell adhesion molecule neuroplastin-65 (Np65). Neurons lacking Np65 exhibit severely impaired LTP maintenance, and Np65 deletion prevents GluA1 from rescuing LTP in AMPARs-deleted neurons. Thus, our study reveals an essential role for GluA1/Np65 binding in anchoring AMPARs at the postsynaptic membrane during LTP.